How to Measure Sustainability in the Supply Chain Design: An Integrated Proposal from an Extensive and Systematic Literature Review - Vasquez-Perez, O; Espinoza-Perez, A (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
The increase in the world population and resource scarcity has led to the introduction of environmental concepts such as sustainability and sustainable supply chain design (SSCD). However, there is a lack of consensus among researchers on how to measure sustainability in SSCD. Therefore, the authors propose a novel approach to measuring sustainability in the context of SSCD by developing an integrated, tractable, and representative metrics framework. The methodology corresponds to a quantitative approach involving bibliographic examination and statistical techniques. First, the authors conducted a systematic literature review by formulating research questions and a search protocol, searched for relevant articles, and conducted a quality assessment on full-text reviews to obtain metrics for measuring sustainability in SSCD from the literature. Then, they defined aggregation criteria representing their inclusion relationship by merging associated metrics. The authors then used Cluster Analysis (CA), a multivariate statistical technique, for grouping the metrics. Consequently, twelve clusters were distinguished from 541 research articles, grouping 51 metrics from different sustainability dimensions. It shows the strong connection among the sustainability dimensions, i.e., they must be assessed holistically. Then, we proposed reducing the 51 metrics to 5 to evaluate sustainability in the SSCD, allowing us to focus on a reduced number of indicators. © 2023 by the authors.